The Impact of Search and Rescue Training and Leadership on Employee Performance: Job Satisfaction as a Mediator Variable in the South Sumatra Regional Marine and Air Police Directorate - Pranata, Andri; Helmi, Sulaiman; Trisninawati; Sartika, Dewi (Sinergi International Journal of Management and Business, 2024)
Human Resource Management (HRM) is a crucial discipline in managing labor relations to achieve organizational goals effectively and efficiently. HRM integrates scientific elements and artistic aspects in managing human resources. The scientific approach focuses on systematic understanding of labor management, while the artistic approach emphasizes talent and skills in influencing individuals to achieve specific objectives. This research aims to explore the impact of Search and Rescue (SAR) training and leadership on employee performance, considering job satisfaction as a mediating factor. The research sample includes 128 personnel of the South Sumatra Regional Marine and Air Police Directorate using a quantitative descriptive analysis method. Data were collected through questionnaires and analyzed using linear regression. The findings indicate that SAR training and leadership significantly affect employee performance, with job satisfaction serving as a crucial mediator. Additionally, 45% of personnel have not attended SAR training, which can negatively impact their performance in emergency situations. These insights are valuable for the management of South Sumatra Regional Marine and Air Police Directorate in enhancing operational effectiveness and employee performance through improved training and effective leadership.